2016
DOI: 10.1177/1524839915622196
|View full text |Cite
|
Sign up to set email alerts
|

Translating an Evidence-Based Injury Prevention Program for Implementation in a Home Visitation Setting

Abstract: Safe N' Sound (SNS), a computer-based childhood injury prevention program, provides individually tailored information to parents about their child's injury risks with specific behavioral recommendations. We translated SNS for implementation in a home visitation organization in order to increase its capacity to effectively address injury prevention and decrease the burden of injury experienced by high-need families. The aim of this study was to identify behavioral and organizational barriers and facilitators to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The included studies described the implementation of various types of EBIs, mostly in a hospital care setting (Table 3). A majority of the articles focused on the implementation of strategies/practices, and within that group, about one-third (n = 11) were different types of e-health initiatives [17,[19][20][21][22][23][24][25][26][27][28]. Almost half of the EBIs tried to improve health outcomes in an organization, whereas the remaining EBIs targeted health outcomes on population level, health system development, and reorganization of care services.…”
Section: Study and Ebi Characteristicsmentioning
confidence: 99%
“…The included studies described the implementation of various types of EBIs, mostly in a hospital care setting (Table 3). A majority of the articles focused on the implementation of strategies/practices, and within that group, about one-third (n = 11) were different types of e-health initiatives [17,[19][20][21][22][23][24][25][26][27][28]. Almost half of the EBIs tried to improve health outcomes in an organization, whereas the remaining EBIs targeted health outcomes on population level, health system development, and reorganization of care services.…”
Section: Study and Ebi Characteristicsmentioning
confidence: 99%
“…Likewise, some studies showed a significant improvement in home safety [ 16 , 17 ], while others did not [ 18 , 19 ]. There have been attempts to explore why results are discrepant [ 20 22 ], but no clear indicators for success have emerged. Outstanding questions remain such as the relative benefit of recruiting in the community or hospital settings, the optimal number of visits, and qualifications to conduct home visits.…”
Section: Introductionmentioning
confidence: 99%